Conflicts and Operational Hurdles in the management of Innovative Projects: an empirical study - Donato, José Varela; Kubo, Edson Keyso de Miranda; Domingues, Carlos Roberto (Revista de Administração da UFSM, 2013)
This article aims at describing how conflicts and operational hurdles manifest themselves in the management of innovative projects in a development bank (DB). The research characterizes itself as a qualitative and exploratory approach; the data collection consisted of interviews with consultants and project managers and by documents on management projects in Development Bank; the interviews have undergone the content analysis by utilizing the Atlas.ti. The research revealed that the project management in its new implemented model faces difficulties similar to those observed in traditional hierarchies. It was observed that conflicts regarding interests, values, psychological aspects and operational hurdles are intrinsic to the life cycle of innovative projects, which implementation requires a lot of political capacity from their leaders to be effective.